An analysis of the transport infrastructure of the Cape Midlands and Karroo regions,Analysis of the transport infrastructure of the Cape Midlands and Karoo regions - Staude, Gavin Ernest (Rhodes University, Faculty of Commerce, Department of Economics, 1973)
From Preface: In 1966, the Karroo Development Association approached Rhodes University to undertake a socio-economic survey of their region. This survey was to form the basis for development planning in view of the expected benefit to the region of the Orange River Project. Similar requests were also received from the Midlands Planning Association and the South Eastern Areas Development Association. When Rhodes University consulted the Department of Planning, which strongly supported the principle of a regional survey, it was decided that, although Port Elizabeth and its hinterland comprised a logical economic unit, the area should be sub-divided. The University of Port Elizabeth was entrusted with the responsibility for an analysis of the metropolitan area, while the Institute of Social and Economic Research of Rhodes University was commissioned to undertake a socio-economic survey of the inland areas. This thesis on the transport infrastructure of the Cape Midlands and Karroo Regions represents one aspect of the survey.
Keywords: Transportation -- South Africa -- Cape of Good Hope; Railroads -- South Africa -- Cape of Good Hope -- History; Railroads -- Construction and development -- South Africa -- Cape of Good Hope -- History; Transportation, Automotive -- South Africa -- Cape of Good Hope; Roads -- Construction and development -- South Africa -- Cape of Good Hope